Gender Differences in Wage Expectations: Sorting, Children, and Negotiation Styles - Lukas Kiessling; Pia Pinger; Philipp Seegers; Jan Bergerhoff (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper presents evidence from a large-scale study on gender differences in expected wages before labor market entry. Based on data for over 15,000 students, we document a significant and large gender gap in wage expectations that closely resembles actual wage differences, prevails across subgroups, and along the entire distribution. To understand the underlying causes and determinants, we relate expected wages to sorting into majors, industries, and occupations, child-rearing plans, perceived and actual ability, personality, perceived discrimination, and negotiation styles. Our findings indicate that sorting and negotiation styles affect the gender gap in wage expectations much more than prospective child-related labor force interruptions. Given the importance of wage expectations for labor market decisions, household bargaining, and wage setting, our results provide an explanation for persistent gender inequalities.
Keywords: D81; D84; I21; I23; J13; J30; 330; subjective wage expectations; gender gap; negotiation styles